Review of the most common knee injuries in basketball - Ikic, T.; Vrdoljak, D.; Penga, L.; Radovcic, N.; Milic, M. (Serbian Journal of Sports Sciences, 2021)
The aim of the study was to determine the incidence and localization of knee pain in female basketball players by applying the newly constructed Questionnaire on the incidence of knee pain and injuries which was filled out anonymously, and to determine the basic metric characteristics of the applied questionnaire, as well as the differences based on chronological age and playing position. The sample of participants included 44 active Croatian female basketball players aged 16 to 39 years. The players` mean chronological age was 23.05±5.28 years, their mean body mass was 67.77±7.34 kg, body height was 176.76±6.35 cm, and body mass index (BMI) was 21.65±1.49 kg•m-2. The Questionnaire on the incidence of knee pain and injuries has good metric characteristics, thus it is a quality instrument for measuring the incidence of pain and injuries in basketball players. The reported incidence of knee pain and injuries in basketball players was at medium level, however, 45% of players reported knee pain and injuries. Out of the total sample of participants, 39% players reported previous knee injuries. There were no significant differences between players in different age groups (younger - under 22 years, and older - over 23 years) regarding the level of incidence of knee pain and injuries in any of the measured variables. Future studies should include more participants, especially more players at "center" position, and include more variables, possibly related to movements in basketball.